Sequestration of Zn into mixed pyrite-zinc sulfide framboids: A key to Zn cycling in the ocean?. (15th November 2018) - Hu, Si-Yu; Evans, Katy; Rempel, Kirsten; Guagliardo, Paul; Kilburn, Matt; Craw, Dave; Grice, Kliti; Dick, Jeffrey
Abstract: Zinc (Zn) is an important micronutrient in the ocean, and fixation of Zn into organic, trace element-rich sediments is an important contributor to Zn cycling in the ocean. Framboidal sulfides are considered to be the major host for Zn in such settings. The sequestration of Zn into framboids via biotic or abiotic processes is not fully understood, which presents difficulties for interpretation of Zn isotope values in sediments. In this work, we describe a novel type of framboid with mixed pyrite and zinc sulfide (sphalerite or wurtzite) microcrystals from meta-pelites of the Otago Schist, New Zealand. A combination of optical microscopy, scanning electron microscopy (SEM) and nanoscale secondary ion mass spectrometry (NanoSIMS) were utilized to assess the association between Zn, pyrite and organic matter in framboids. The distribution of Zn in framboids is variable. Most pyrite microcrystals include minor amounts of Zn. Trace Zn is also observed to co-locate with organic matter, which occurs on the boundaries of pyrite microcrystals. Finally, Zn is found as single zinc sulfide microcrystals or zinc sulfide rims around pyrite microcrystals within individual framboids. These textures have not been recorded before, to our knowledge. The sequence of events that sequesters Zn into framboids may affect Zn isotope fractionation from seawater to continental margin sediments.